(untitled) (Research, Society and Development, 2021)
Studies of economic valuation of environmental resources are approximate propositions in monetary terms for natural assets that they do not have market value. This work aims to estimate the economic value of the waterfall complex in Presidente Figueiredo, municipality in the state of Amazonas, Brazil. Using environmental economics references, we sought to identify the effects of the lack of value of the set of assets that make up this natural heritage. The research is quantitative in nature and the method used was Contingent Valuation. 257 samples were collected, obtained through interviews and questionnaires. With the help of the beta variable, it was estimated, on average, that visitors would be willing to contribute to the hypothetical improvements to be implemented in the Presidente Figueiredo waterfall complex (CCPF), both in terms of infrastructure and biodiversity conservation with approximately 13 % of your daily income. This reveals an environmental heritage of approximately R35,000,000.00, and a potential income of R4,000,000.00 annually.